2009
DOI: 10.1055/s-0029-1214896
|View full text |Cite
|
Sign up to set email alerts
|

Degree of concordance between double-balloon enteroscopy and capsule endoscopy in obscure gastrointestinal bleeding: a multicenter study

Abstract: Capsule endoscopy and DBE have good agreement for vascular and inflammatory lesions but not for polyps or neoplasia. DBE provides valuable adjunctive information, particularly in patients with neoplasia or polyp at capsule endoscopy. DBE clarified the origin of bleeding in two-thirds of patients with capsule endoscopy showing only blood in the lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 17 publications
3
57
2
4
Order By: Relevance
“…CE-based diagnosis can be controversial because it depends only on gross findings. According to a multicenter study, the degree of concordance between CE and DBE is above 0.7 for vascular or inflammatory lesions, while it is only 0.46 for tumors [18]. In this study, biopsies were performed in three-fourths of the patients with small bowel tumors, and histopathological diagnosis was consistent with gross diagnosis in 72.9% of these cases.…”
Section: Discussionmentioning
confidence: 69%
“…CE-based diagnosis can be controversial because it depends only on gross findings. According to a multicenter study, the degree of concordance between CE and DBE is above 0.7 for vascular or inflammatory lesions, while it is only 0.46 for tumors [18]. In this study, biopsies were performed in three-fourths of the patients with small bowel tumors, and histopathological diagnosis was consistent with gross diagnosis in 72.9% of these cases.…”
Section: Discussionmentioning
confidence: 69%
“…In 2009, Fukumoto et al [18] reported finding an ileal diverticulum on DBE that was missed by VCE. Marmo et al [19] reported two missed jejunal diverticula that were later seen on subsequent DBE. Similarly, Arakawa et al [20] reported 2 cases of diverticulosis of the small bowel that were missed at previous VCE.…”
Section: Discussionmentioning
confidence: 99%
“…Angioectasia detected at DBE but not at VCE has also been described. Arakawa and Marmo each reported 2 VCE-negative DBE-positive cases [19,20] . None of these studies, however, assessed the test characteristics of VCE using DBE as the criterion standard.…”
mentioning
confidence: 99%
“…However, the introduction of CE and DBE has led to increased detection rates of small bowel tumors, which are identified in 7% to 17.4% patients with OGIB [7][8][9][10] . According to the report, small bowel tumors included GIST (28.6% to 32.1%), adenocarcinomas (20.5% to 25%), neuroendocrine tumor (14.3% to 15.2%), malignant lymphomas (10.7% to 14.3%), adipose tumors (8.9%), metastatic tumors (10.7%), and Kaposi sarcoma (3.6%) [11,12] .…”
Section: Discussionmentioning
confidence: 99%